Perencanaan Design Geometri Peledakan Berdasarkan Karakteristik Massa Batuan di Bench M PT Tanjung Bukit Nunggal Kabupaten Bangka Tengah - Armansyah Putra Sinulingga; Franto Franto; Janiar Pitulima (MINERAL, 2022)
The availability of the discontinuity structure causes the rock to be blown up have a cavity that later can be traversed by the thumping of explosive energy, so force from the explosion will be inhibited and the blasting is not optimal. This study aims to find the physical condition of granite rock at the mining site, find out the value of Blastibality Index of rock, and analyze the geometry design of blasting to obtain fragmentation ≤ 75 cm. The methods used in this study are quantitative and qualitative methods that are measuring joint structures, physical conditions of rocks, calculation of Rock Factor (RF) values, and calculation of Blastibility Index. The results of this study show if the physical condition of the rocks on bench M has an RQD value 88.97 % - 99.66 %, and Rock Factor value 5.51 and a Blastability Index 45.9 so, obtained a design of geometry with a burden 3.4 m, spacing 5.1 m, stemming 2.55 m, subdrilling 0.68 m, height 7.62 m, depth 5.1 m, and power charging 2.55 m.